Hyperostosis frontalis interna – a find in women individual from Modern Times (St. Martin Cathedral, Spisska Kapitula, Slovakia) - Eva Petrušová Chudá; Michaela Dörnhöferová (AntropoWebzin, 2011)
In this study we present find of skeletal remains from the St. Martin Cathedral from the 17th – 18th centuries which were excavated in year 2008. Especially of individual from grave no. 2/2008 – preserved cranium showed marks of endocranial hyperostosis (stage B according Hershkovitz et al. 1999). Hyperostosis frontalis interna (HFI) is an overgrowth of bony tissue on the inner plate of the frontal bone of the calvaria, the irregular thickening of the endocranium (may be 1 cm or thicker). It is typically bilateral and symmetrical, and may extend to involve the parietal bones. It was first described in 1765 by Morgagni and Santorini as an obesity and virilism associated with thickening of internal table of the frontal bone called hyperostosis frontalis interna. HFI appears more commonly in women than in men, with an estimated male:female ratio 1:9, usually in age 35 years and older women. In modern population this condition is most prevalent in postmenopausal females, with frequencies of 40 – 62% reported, in general population, composed of males and females of different ages HFI affects 3 – 15% of individuals. In contrast, HFI is rarely reported in an archeological context. Using an anthropomorphological and paleopathological examination of the skeletal remains we realized that this women was in age category adultus II (30 – 39 years) or older, her stature was cca 151.875 cm and she also suffered from DISH, healed fracture of styloid process of right ulna, osteoarthrosis of humeral and femoral heads and spondylosis.